Pelaksanaan KKN Terintegrasi PPL KE-02 Mahasiswa UIN Alauddin Makassar di Kota Bandung - Iqbal, Muhammad; Shalihah, Nurul Imraatu; Aslinda, Yeyen; Muharram, Fathan; Arman, Sitti Nurannisa; Ziaul Haq, Achmed; Sekarwangi Putri, Evhy; Mubarak, Kasyful; Adriani, Andi Dian; Syam, Nurul Inayah (Yayasan Daarul Huda Kruengmane, 2025)
Real Work Lecture (KKN) is a regular agenda in the field of service to society conducted by students of UIN Alaudin Makassar under the appointed Guiding Lecturer KKN. KKN became a vessel for learning about how to be part of society and became our own space for us students to practice firsthand the sciences and theories that have been obtained from the lecture bench, in Rancameong, Babakan Penghulu Village, Bandung District, Cinambo District. The activities carried out in are activities based on the survey results and potential and existing problems in the KKN location. The activities contribute actively in solving problems of the Village which include raising legal, educational, religious, social, and health awareness. As for the work program that has been implemented namely the Festival of righteous children, Legal Counseling, Teaching Learning, Devotional Work, and Gymnastics together these work programs have been successfully implemented thanks to the collaboration between KKN students from UIN Alauddin Makassar and the entire talent community Ranhulume Village, Bandung City.